Submerged arc weld joint and manufacturing method thereof

By adjusting the welding metal composition and optimizing the welding process parameters, the problem of difficult to ensure the strength and toughness of welding metals in multi-layer latent arc welding is solved, and efficient and high-quality welding results are achieved.

JP2025058892AActive Publication Date: 2025-04-09JFE STEEL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024108643
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2024-07-05
Publication Date
2025-04-09
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

The prior art is difficult to ensure the strength and toughness of the welded metal in multi-layer latent arc welding of high-strength steel, and there is also the problem of low construction efficiency.

Method used

By adjusting the composition of the welded metal, ensure that Ceq and SRI are within a specific range, and combining elements such as Si, Cr and Mo, the hardening and anti-softening properties of the welded metal are improved, while optimizing welding process parameters such as heat input and path temperature.

Benefits of technology

The high strength and high toughness of the welded metal in multi-layer latent arc welding is achieved, and the construction efficiency is improved, ensuring that the strength of the welded metal reaches 500MPa or above and the toughness reaches 47J or above.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058892000001_ABST
    Figure 2025058892000001_ABST
Patent Text Reader

Abstract

To provide a weld joint which satisfies required strength and toughness required with high execution efficiency in multi-layer submerged arc welding.SOLUTION: A composition of a weld metal contains C of 0.04 to 0.12 mass%, Si of 0.10 to 0.50 mass%, Mn of 1.0 to 1.8 mass%, P of 0.025 mass% or less, S of 0.015 mass% or less, Cr of 0.2 to 1.0 mass%, Mo of 0.2 to 1.0 mass%, Ti of 0.002 to 0.070 mass%, B of 0.0004 to 0.0025 mass%, O of 0.050 mass% or less, N of 0.008 mass% or less, and the remainder comprising Fe and inevitable impurities, Ceq represented by the formula (1) of Ceq=C+Si / 24+Mn / 6+Ni / 40+Cr / 5+Mo / 4+V / 14 is 0.44 to 0.56 mass%, and SRI represented by the formula (2) of SRI=[Si]×[Cr]×[Mo]×1000 is 30 or more.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a submerged arc welded joint, and in particular to a multi-pass submerged arc welded joint in which the welding heat input in the final pass is 100 kJ / cm or more for high tensile steel with a yield strength of 500 MPa class for architectural structures, and to a method for manufacturing the same. [Background technology]

[0002] In recent years, the trend toward larger and longer span architectural structures has led to a trend toward higher strength steel plates for steel frames. Conventionally, the strength class of steel for skin plates in box columns was mainly 440 MPa yield strength and 590 MPa tensile strength, but recently, 590 MPa steel with a yield strength of 500 MPa has come to be used.

[0003] Submerged arc welding is generally used for joining skin plates of box columns. In particular, for skin plates with a thickness of 70 mm or more, a multi-pass submerged arc welding method with a high heat input of 100 kJ / cm or more for each pass (hereinafter simply referred to as "heat input") has been proposed.

[0004] For example, Patent Document 1 describes an extremely thick welded member that is welded by multi-layer submerged arc welding in which the heat input of the first layer is 300 kJ / cm or more and the second pass weld metal is not in contact with the base metal. This aims to prevent insufficient fusion that is likely to occur between the inner wall of the groove by setting the second pass welding target position at the center of the groove and dissolving hot cracks that may occur in the first layer weld metal in the second pass welding and welding the second pass weld metal only onto the first layer weld metal.

[0005] Patent Document 2 describes a multi-layer submerged arc welding method for extra-thick steel plates, in which slag is left behind after the first layer is welded, the entire work is covered with a heat insulating material to keep it warm for a specified time, the second layer is welded, and then the next layer is welded a certain time after the end of welding. This promotes a reduction in the amount of diffusible hydrogen in the weld metal and prevents low-temperature cracking that is likely to occur in the second and subsequent layers.

[0006] Patent Document 3 describes a welding method in which, in multi-pass submerged arc welding with a first-pass heat input of 200 kJ / cm or more, a flux containing a specified amount of iron powder is used, the weld metal contains specified amounts of B and Mo, and the weld crack susceptibility composition Pcm is within a specified range. This is intended to reduce the grain boundary ferrite structure generated in the weld metal and suppress grain boundary precipitation, thereby suppressing low-temperature cracking, etc. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2004-276117 A [Patent Document 2] JP 2014-217855 A [Patent Document 3] JP 2018-65152 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, the method of Patent Document 2 requires a long hold time between passes of 2 to 6 hours, which leads to a decrease in construction efficiency.In addition, it was found that the welding methods of Patent Documents 1 and 3 cannot ensure the required strength of the weld metal when multi-layer submerged arc welding high-tensile steel with a yield strength (0.2% proof stress) of 500 MPa class is performed.

[0009] In view of the above circumstances, an object of the present invention is to provide a welded joint which satisfies the strength and toughness required for multi-pass submerged arc welding with high process efficiency.

[0010] The required weld metal strength here means that the yield strength is 500 MPa or more and the tensile strength is 590 MPa or more in a room temperature tensile test of a tensile test piece with a parallel section diameter of 12.5 mmφ taken from a position 10 mm below the steel plate surface at the center of the groove width of the weld metal (see Figure 3). Also, in order to ensure the required weld metal toughness, a Charpy impact test is conducted on a V-notch Charpy impact test piece taken from a position 7 mm below the steel plate surface at the center of the groove width of the weld metal (see Figure 4), with the target absorbed energy at a test temperature of 0°C being 47 J or more. The absorbed energy at a test temperature τ°C is hereinafter referred to as " V It is expressed as "Eτ℃". [Means for solving the problem]

[0011] In order to achieve high construction efficiency, the inventors have studied submerged arc welded joints with interpass temperatures of 150±10°C and heat input of 100 kJ / cm or more in all passes. As a result, in the conventional technology, the reheating of the final pass softens the weld metal of the previous pass, causing a decrease in strength, and it was not possible to ensure a yield strength of 500 MPa or more in a tensile test at a test piece taken from the center of the groove width of the weld metal 10 mm below the surface. Therefore, further studies were conducted to ensure the hardenability of the weld metal and to suppress softening by adding Si, Cr, and Mo to the weld metal in combination. That is, when Ceq shown in the following formula (1) is 0.44 to 0.56% and SRI shown in the following formula (2) is 30 or more, softening due to reheating of the final pass is suppressed and the required strength of the weld metal is ensured. Ceq=C+Si / 24+Mn / 6+Ni / 40+Cr / 5+Mo / 4+V / 14 ‥‥(1) SRI=[Si]×[Cr]×[Mo]×1000 ‥‥(2) In formula (1), C, Si, Mn, Ni, Cr, Mo, and V represent the content (mass%) of each element in the composition of the weld metal, and the content of elements that are not contained is 0. In formula (2), [Si], [Cr], and [Mo] represent the numerical value (dimensionless) of mass% of each element.

[0012] The present invention was completed based on the above findings and through further investigation, and the gist of the present invention is as follows. [1] In multi-pass submerged arc welded joints, The composition of the weld metal is in mass percent. C: 0.04-0.12%, Si: 0.10 to 0.50%, Mn: 1.0-1.8%, P: 0.025% or less, S: 0.015% or less, Cr: 0.2-1.0%, Mo: 0.2-1.0%, Ti: 0.002 to 0.070%, B: 0.0004~0.0025%, O: 0.050% or less, A submerged arc welded joint comprising: N: 0.008% or less, with the balance being Fe and unavoidable impurities; Ceq as represented by the following formula (1) being 0.44-0.56%; and SRI as represented by the following formula (2) being 30 or more. Ceq=C+Si / 24+Mn / 6+Ni / 40+Cr / 5+Mo / 4+V / 14 ‥‥(1) SRI=[Si]×[Cr]×[Mo]×1000 ‥‥(2) In formula (1), C, Si, Mn, Ni, Cr, Mo, and V represent the content (mass%) of each element in the composition of the weld metal, and the content of elements that are not contained is 0. In formula (2), [Si], [Cr], and [Mo] represent the numerical value (dimensionless) of mass% of each element. [2] The composition of the weld metal is further comprised in mass percent: The submerged arc welded joint according to [1], characterized in that it contains one or more of Cu: 0.60% or less, Ni: 1.8% or less, V: 0.05% or less, Nb: 0.05% or less, and Al: 0.05% or less. [3] A submerged arc welded joint as described in [1] or [2], characterized in that the width of the heat-affected zone within 10 mm of the surface formed by the final welding pass is 5 mm or more. [4] In the method for producing a submerged arc welded joint according to the above [1], The composition of the welding wire is expressed as mass percent. C: 0.02-0.14%, Si: 0.02 to 0.80%, Mn: 1.0-2.3%, P: 0.025% or less, S: 0.015% or less, Mo: 0.2-1.0%, O: 0.020% or less, N: Contains 0.010% or less, with the balance being Fe and unavoidable impurities; The composition of the welding flux is in mass percent, SiO2: 8-30%, MgO: 10-30%, CaO: 1-10%, CaF2: 1-10%, Al2O3: 5-20%, TiO2: 2-10%, Na2O: 1.0-3.0%, B2O3: 0.1-0.5%, Total of one or more metal carbonates in terms of CO2: 2 to 12% Fe: 15-30%, Si: 0.1 to 2.0%, Mn: 0.1-2.0%, A method for producing a submerged arc welded joint, comprising the steps of: (a) forming a steel sheet having a Cr content of 0.1 to 4.0%; and (b) forming a balance of unavoidable impurities. [5] In the method for producing a submerged arc welded joint according to the above [2], The composition of the welding wire is expressed as mass percent. C: 0.02-0.14%, Si: 0.02 to 0.80%, Mn: 1.0-2.3%, P: 0.025% or less, S: 0.015% or less, Mo: 0.2-1.0%, O: 0.020% or less, N: Contains 0.010% or less, Further, it contains one or more of Cu: 1.00% or less, Ni: 2.5% or less, Cr: 1.0% or less, V: 0.10% or less, Nb: 0.10% or less, Al: 0.05% or less, Ti: 0.060% or less, and B: 0.0050% or less, with the balance being Fe and unavoidable impurities; The composition of the welding flux is in mass percent, SiO2: 8-30%, MgO: 10-30%, CaO: 1-10%, CaF2: 1-10%, Al2O3: 5-20%, TiO2: 2-10%, Na2O: 1.0-3.0%, B2O3: 0.1-0.5%, Total of one or more metal carbonates in terms of CO2: 2 to 12% Fe: 15-30%, Si: 0.1 to 2.0%, Mn: 0.1-2.0%, Cr: 0.1 to 4.0% The method for producing a submerged arc welded joint further comprises one or more of the following: Ni: 3.0% or less, Mo: 2.0% or less, Al: 1.0% or less, and Ti: 1.0% or less, with the remainder being unavoidable impurities. Effect of the Invention

[0013] According to the present invention, in multi-layer submerged arc welding, it is possible to obtain a yield strength of 500 MPa or more, a tensile strength of 590 MPa or more, and V E0℃: Toughness of 47J or more This makes it possible to secure a weld metal having a high quality, which is particularly advantageous in industry. [Brief description of the drawings]

[0014] [Figure 1] FIG. [Diagram 2] FIG. 2 is a schematic diagram showing a cross section of a welded joint. [Diagram 3]FIG. 2 is a schematic diagram showing positions at which tensile test specimens were taken from the weld metal. [Figure 4] FIG. 2 is a schematic diagram showing positions at which Charpy test pieces were taken from the weld metal. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention will be described. [Multi-layer submerged arc welded joints] The present invention aims to provide a welded joint that satisfies the required strength and toughness under high processing efficiency in multi-layer submerged arc welding, where the multi-layer submerged arc welding may be performed by one pass per layer or two or more passes per layer. [Preferable welding conditions] In the present invention, in order to ensure high construction efficiency, mechanical properties of the joint, and good weld beads, the following construction conditions are preferred. [Heat input of final welding pass: 100kJ / cm or more] To ensure high construction efficiency, the heat input of the final welding pass is preferably 100 kJ / cm or more. However, if it exceeds 200 kJ / cm, the strength and toughness of the joint may become insufficient, so the heat input is more preferably 100 to 200 kJ / cm. [Heat input for welding passes other than the final pass: 100~700kJ / cm] If the heat input of the welding pass other than the final welding pass is less than 100 kJ / cm, the construction efficiency may be insufficient. On the other hand, if it exceeds 700 kJ / cm, the strength and toughness of the joint may be insufficient or the weld bead shape may be poor. Therefore, the heat input of the welding pass other than the final welding pass is preferably 100 to 700 kJ / cm. More preferably, it is 150 to 550 kJ / cm. [Interpass temperature: 50~300℃] If the interpass temperature is less than 50°C, it takes time for the interpass temperature to drop, which reduces the efficiency of application, while if it exceeds 300°C, it may result in insufficient strength. Therefore, the interpass temperature is preferably 50 to 300°C, and more preferably 100 to 250°C. [Base material thickness: 65~100mm, yield strength: 500MPa or more, tensile strength: 590MPa or more] Considering application to the skin plate of a box column, the plate thickness of the base material is preferably 65 to 100 mm, and the yield strength and tensile strength of the base material are preferably 500 MPa or more and 590 MPa or more, respectively. If the tensile strength of the base material is too high, the toughness of the base material may become insufficient, so the tensile strength of the base material is more preferably 590 to 740 MPa. [Group shape] The groove shape is not particularly limited, but examples include a two-stage V groove shape with a root face of 0 to 5 mm, a first stage groove angle of 20 to 40°, and a second stage groove angle of (first stage groove angle + 0°) to 40°.

[0016] [Weld metal composition] In order to achieve the above object, in the present invention, it is necessary to add elements that contribute to improving strength, such as C, Si, Mn, Ni, Cr, Mo, and V, to the weld metal and adjust Ceq and SRI within specific ranges. The composition of the weld metal and the reasons for limiting the ranges thereof will be described below. Note that in the composition of the weld metal, the unit "%" for the content of each component means "mass %." [C: 0.04~0.12%] C is an element that improves the strength of the weld metal, and has a large influence. If the C content in the weld metal is less than 0.04%, the strength of the weld metal is insufficient. On the other hand, if it exceeds 0.12%, the weld metal hardens and cold cracks occur. Therefore, the C content is limited to the range of 0.04 to 0.12%. The C content is preferably 0.05 to 0.10%. [Si: 0.10~0.50%] Silicon acts as a deoxidizing element in the weld metal and reduces the amount of dissolved oxygen, thereby contributing to improving the toughness of the weld metal, but this effect is poor at less than 0.10%, while at more than 0.50%, it promotes the formation of a hard second phase in the weld metal, deteriorating the toughness. For this reason, the silicon content is limited to the range of 0.10 to 0.50%, and preferably 0.15 to 0.45%. [Mn: 1.0-1.8%] Mn is an element that improves hardenability, and must be added at 1.0% or more to ensure the strength of the weld metal. On the other hand, if it exceeds 1.8%, the strength becomes too high and low-temperature cracking occurs. Therefore, Mn is limited to 1.0 to 1.8%. It is preferably 1.1 to 1.7%. [P:0.025% or less] P is an element that segregates at grain boundaries in weld metal and induces hot cracking, and in the present invention, it is preferable to reduce it as much as possible, but 0.025% or less is acceptable. Therefore, P is limited to 0.025% or less. However, excessive reduction leads to high costs for welding materials. Therefore, P is preferably adjusted to 0.003% or more. [S:0.015% or less] S is an element that segregates at grain boundaries in weld metal and induces hot cracking, and in the present invention, it is preferable to reduce it as much as possible, but 0.015% or less is acceptable. Therefore, S is limited to 0.015% or less. However, excessive reduction leads to high costs for welding materials. Therefore, S is preferably adjusted to 0.002% or more. [Cr: 0.2~1.0%] Cr is an element that is effective in improving strength and also improves softening resistance, and is an essential addition in the present invention. However, if the Cr content is less than 0.2%, the above effects of Cr are not exhibited, while if the Cr content exceeds 1.0%, the formation of a hard second phase is promoted, and the toughness of the weld metal decreases. Therefore, the Cr content is limited to 0.2 to 1.0%, and preferably 0.2 to 0.8%. [Mo: 0.2-1.0%] Mo is an element effective in improving strength, and is also effective in suppressing grain boundary ferrite, which is a low-toughness structure, and is therefore added as an essential element in the present invention. However, if the Mo content is less than 0.2%, the above-mentioned effects of Mo are not exhibited, while if the Mo content exceeds 1.0%, the strength of the weld metal becomes too high, causing low-temperature cracking. For this reason, Mo is limited to the range of 0.2 to 1.0%, and preferably 0.4 to 0.9%. [Ti: 0.002~0.070%] Ti acts as a deoxidizing element in the weld metal and reduces the amount of dissolved O. It also reduces the interfacial energy between oxides and molten steel, finely dispersing the oxides, thereby contributing to improving the toughness of the weld metal. If the content is less than 0.002%, the above effect is not achieved, while if it exceeds 0.070%, the amount of dissolved Ti in the weld metal increases, decreasing the toughness. For this reason, the Ti content is limited to the range of 0.002 to 0.070%. The Ti content is preferably 0.005 to 0.040%. [B:0.0004~0.0025%] B is an element that suppresses low-toughness grain boundary ferrite and contributes to improving the toughness of the weld metal. If the content is less than 0.0004%, the above effect of B is not manifested, while if the content exceeds 0.0025%, hot cracking is induced. Therefore, the B content is limited to the range of 0.0004 to 0.0025%. [O:0.050% or less] O is an impurity that is inevitably mixed into the weld metal and reduces toughness by forming oxides. Therefore, it is preferable to reduce O as much as possible, but in the present invention, O is permissible if it is 0.050% or less, so it is limited to 0.050% or less. [N:0.008% or less] N is an impurity that is inevitably mixed into the weld metal and deteriorates the toughness of the weld metal. Therefore, it is preferable to reduce it as much as possible, but in the present invention, a content of 0.008% or less is acceptable, so it is limited to 0.008% or less. In the present invention, one or more of Cu, Ni, V, Nb and Al may be selectively added to the composition of the weld metal within the following ranges.

[0017] [Cu:0.60% or less] Cu is an element that finely precipitates in the weld metal and improves strength through precipitation strengthening, and since this effect is remarkable at 0.05% or more, when added, 0.05% or more is preferable. On the other hand, Cu exceeds 0.60%, red brittleness is exhibited and bead surface cracks are induced, so 0.60% or less is preferable. The more preferable range is 0.05 to 0.50%. [Ni:1.8% or less] Ni is an effective element in increasing the strength of weld metal without decreasing toughness, and such an effect is remarkable at 0.1% or more, so when added, 0.1% or more is preferable. On the other hand, Ni is preferably 1.8% or less, because if it exceeds 1.8%, the strength becomes too high and low-temperature cracking occurs. More preferably, it is 0.2 to 1.6%. [V:0.05% or less] V is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating fine carbides in the weld metal, and this effect is remarkable at 0.01% or more, so if added, 0.01% or more is preferable. However, if V exceeds 0.05%, a hardened part is formed during reheating, and low-temperature cracking occurs, so 0.05% or less is preferable. More preferably, it is 0.01 to 0.04%. [Nb:0.05% or less] Nb is an element that improves hardenability and contributes to improving the strength of the weld metal, and this effect is remarkable at 0.01% or more, so if added, 0.01% or more is preferable. However, if Nb exceeds 0.05%, a hardened part is formed during reheating and low-temperature cracking occurs, so 0.05% or less is preferable. More preferably, it is 0.01 to 0.04%.

[0018] [Al: 0.05% or less] Al acts as a deoxidizing element in the weld metal, and reduces the amount of dissolved O, thereby reducing oxides and contributing to high toughness of the weld metal, and this effect is remarkable at 0.01% or more, so if added, 0.01% or more is preferable. On the other hand, if Al exceeds 0.05%, coarse bainite structures are formed in the weld metal, reducing toughness, so 0.05% or less is preferable. More preferably, it is 0.01 to 0.04%. In the composition of the weld metal, the balance other than the above-mentioned components consists of Fe and unavoidable impurities.

[0019] In the present invention, in order to ensure the required strength of the weld metal, not only the above-mentioned range of the composition of the weld metal is satisfied, but also Ceq expressed by formula (1) and SRI expressed by formula (2) need to satisfy the following conditions. Ceq=C+Si / 24+Mn / 6+Ni / 40+Cr / 5+Mo / 4+V / 14 ‥‥(1) SRI=[Si]×[Cr]×[Mo]×1000 ‥‥(2) In formula (1), C, Si, Mn, Ni, Cr, Mo, and V represent the content (mass%) of each element in the composition of the weld metal, and the content of elements that are not contained is 0. In formula (2), [Si], [Cr], and [Mo] represent the numerical value (dimensionless) of mass% of each element.

[0020] [Ceq: 0.44-0.56%, SRI: 30 or higher] The reason why Ceq is 0.44% or more is to ensure the hardenability of the weld metal and to satisfy the yield strength of 500 MPa or more and the tensile strength of 590 MPa or more, but if it exceeds 0.56%, the strength becomes excessive and low-temperature cracking is induced. The preferable range is 0.46 to 0.53%. The SRI is an index showing temper softening resistance, and the combined addition of Si, Cr, and Mo is effective in suppressing softening, and if the SRI is 30 or more, sufficient temper softening resistance is exhibited and the weld metal can ensure a yield strength of 500 MPa or more. Note that if the SRI exceeds 150, a hard second phase may be formed, causing a decrease in toughness, so a range of 30 to 150 is preferable. [Width of heat-affected zone] In the submerged arc welded joint of the present invention, the width of the heat-affected zone 10 mm from the surface formed by the final welding pass is preferably 5 mm or more. If the width of the heat-affected zone is less than 5 mm, the heat input is small and the construction efficiency may be insufficient. If the width of the heat-affected zone exceeds 12 mm, the heat input is too large and the strength may not be ensured, so the width of the heat-affected zone is more preferably 5 to 12 mm. [Welding materials] In the manufacturing method of the submerged arc welded joint of the present invention, in order to obtain a weld metal composition suitable for the present invention, it is preferable to specify the compositions and ranges of the welding wire and flux as follows. Note that in the compositions of the welding wire and flux, the unit of component content "%" means "mass %". [Welding Wire Composition] The composition of the welding wire and the reasons for limiting the range of the composition will be described below. [C:0.02~0.14%] C is an element that improves the strength of the weld metal, and has a large influence. If the C content in the welding wire is less than 0.02%, the strength of the weld metal is insufficient. On the other hand, if it exceeds 0.14%, the welding wire hardens, the wire feedability during welding deteriorates, and the weld metal hardens, causing low-temperature cracking. Therefore, C is limited to the range of 0.02 to 0.14%. Preferably, it is 0.04 to 0.12%. [Si: 0.02~0.80%] Si acts as a deoxidizing element in the weld metal and reduces the amount of dissolved O, thereby contributing to improving the toughness of the weld metal. For this reason, the content is limited to 0.02% or more. On the other hand, if it exceeds 0.80%, it promotes the formation of a hard second phase in the weld metal, deteriorating the toughness. For this reason, the Si content is limited to the range of 0.02 to 0.80%. The Si content is preferably 0.04 to 0.70%. [Mn: 1.0~2.3%] Mn is an element that enhances hardenability, and 1.0% or more is required to ensure the strength of the weld metal. On the other hand, if it exceeds 2.3%, the welding wire hardens, the feedability deteriorates, and the strength of the weld metal becomes too high, causing low-temperature cracking. Therefore, Mn is limited to 1.0 to 2.3%, and preferably 1.1 to 2.1%. [P:0.025% or less] P is an element that segregates at grain boundaries in the weld metal and induces hot cracking, and in the present invention, it is preferable to reduce it as much as possible, but 0.025% or less is acceptable. Therefore, P is limited to 0.025% or less. However, excessive reduction leads to high costs for the welding wire. Therefore, P is preferably adjusted to 0.003% or more. [S:0.015% or less] S is an element that segregates at grain boundaries in the weld metal and induces hot cracking, and in the present invention, it is preferable to reduce S as much as possible, but 0.015% or less is acceptable. Therefore, S is limited to 0.015% or less. However, excessive reduction leads to high costs for the welding wire. Therefore, S is preferably adjusted to 0.002% or more. [Mo: 0.2-1.0%] Mo is an element effective in improving strength and in suppressing the formation of grain boundary ferrite, which is a low-toughness structure, and is preferably added in an amount of 0.2% or more. On the other hand, if it exceeds 1.0%, the strength of the weld metal becomes too high and low-temperature cracking occurs. Therefore, Mo is limited to the range of 0.2 to 1.0%, and more preferably, 0.3 to 0.9%. [O: 0.020% or less] O is an impurity that is inevitably mixed into welding wire and reduces wire manufacturability by forming oxides. Therefore, it is preferable to reduce the O content as much as possible, but since it is permissible if it is 0.020% or less, it is limited to 0.020% or less.

[0021] [N:0.010% or less] N is an impurity that is inevitably mixed into welding wire. It deteriorates the toughness of the weld metal, so it is preferable to reduce the N content as much as possible. However, since N content of 0.010% or less is permissible, the content is limited to 0.010% or less. In the present invention, one or more of Cu, Ni, Cr, V, Nb, Al, Ti and B may be selectively added to the composition of the welding wire within the following ranges. [Cu:1.00% or less] Cu is an element that finely precipitates in the weld metal and improves strength through precipitation strengthening. Such an effect is remarkable when the Cu content in the welding wire is 0.05% or more. On the other hand, when the Cu content in the welding wire exceeds 1.00%, the weld metal exhibits red brittleness, inducing bead surface cracks. Therefore, the Cu content in the welding wire is preferably 1.00% or less. More preferably, it is 0.05 to 0.80%. [Ni:2.5% or less] Ni is an effective element for increasing the strength of the weld metal without reducing its toughness. This effect is remarkable when the Ni content in the welding wire is 0.1% or more. On the other hand, when the Ni content in the welding wire exceeds 2.5%, the strength of the weld metal becomes too high and low-temperature cracking may occur. Therefore, the Ni content in the welding wire is preferably 2.5% or less. More preferably, it is 0.2 to 2.0%. [Cr:1.0% or less] Cr is an element that is effective in improving the strength of the weld metal and also improves the softening resistance. Cr must be 0.1% or more in the weld metal composition, but it can also be added from the welding flux, so it is not necessarily required to add it from the welding wire. On the other hand, if the Cr content in the welding wire exceeds 1.0%, the welding wire will harden and the feedability will deteriorate, which may cause welding defects. Therefore, the Cr content in the welding wire is preferably 1.0% or less. More preferably, it is 0.1 to 0.9%. [V:0.10% or less] V is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating fine carbides in the weld metal. To obtain such an effect, the V content in the welding wire is preferably 0.01% or more. However, if the V content in the welding wire exceeds 0.10%, a hardened part may be formed in the weld metal during reheating, which may cause low-temperature cracking. Therefore, the V content in the welding wire is preferably 0.10% or less. More preferably, it is 0.02 to 0.09%. [Nb:0.10% or less] Nb is an element that enhances hardenability and contributes to improving the strength of the weld metal. This effect is remarkable when the Nb content in the welding wire is 0.01% or more. However, when the Nb content in the welding wire is 0.10%, a hardened part is formed in the weld metal during reheating, and low-temperature cracking may occur. Therefore, the Nb content in the welding wire is preferably 0.10% or less. More preferably, it is 0.02 to 0.09%. [Al: 0.05% or less] Al acts as a deoxidizing element in the weld metal, and reduces the amount of dissolved O, thereby reducing oxides and contributing to high toughness of the weld metal. Such an effect is remarkable when the Al content in the welding wire is 0.01% or more. On the other hand, when the Al content in the welding wire exceeds 0.05%, coarse bainite structures are formed in the weld metal, and the toughness may decrease. Therefore, the Al content in the welding wire is preferably 0.05% or less. More preferably, it is 0.01 to 0.04%. [Ti:0.060% or less] Ti acts as a deoxidizing element in the weld metal and reduces the amount of dissolved O. It also reduces the interfacial energy between oxides and molten steel and finely disperses the oxides, thereby contributing to improving the toughness of the weld metal. To obtain such an effect, it is preferable to add 0.005% or more. On the other hand, if it exceeds 0.060%, the ductility and toughness decrease due to the increase in the amount of dissolved Ti in the weld metal. Therefore, Ti is preferably limited to 0.060% or less. The content is preferably 0.010 to 0.060%.

[0022] [B:0.0050% or less] B is an element that suppresses low-toughness grain boundary ferrite and contributes to improving the toughness of the weld metal. To obtain this effect, it is preferable to add 0.0005% or more. However, if the content exceeds 0.0050%, wire manufacturability deteriorates. Therefore, B is preferably set to 0.0050% or less. The balance other than the above components consists of Fe and unavoidable impurities. [Welding wire manufacturing method] The welding wire used in the present invention is manufactured, for example, by melting and casting molten steel having a welding wire composition suitable for the present invention, heating and hot rolling it, and cold rolling it to form a wire rod, and then drawing it to the welding wire diameter. The heating temperature and welding wire diameter of the hot rolling are not particularly limited, but examples include a heating temperature of 900 to 1200°C and a welding wire diameter of 4.0 to 6.4 mmφ. [Welding flux composition] The composition of the welding flux (hereinafter, simply referred to as "flux") and the reasons for limiting the range of the composition will be described below. [SiO2: 8~30%] SiO2 is an important component for forming a good weld bead, but if the SiO2 content in the flux is less than 8%, the bead toe will not fit well and undercut will occur. On the other hand, if it exceeds 30%, the oxygen content of the weld metal will increase and toughness will deteriorate. Therefore, the SiO2 content in the flux is limited to 8-30%. It is preferably 12-28%. [MgO: 10~30%] MgO has the effect of improving the basicity of the slag and reducing the oxygen content of the weld metal, but if the MgO content in the flux is less than 10%, the oxygen content of the weld metal increases and the toughness deteriorates. On the other hand, if it exceeds 30%, the softening point of the flux becomes high, the bead height becomes non-uniform, the bead appearance deteriorates, and the slag removability also deteriorates. Therefore, the MgO content in the flux is limited to 10-30%, and preferably 12-28%. [CaO: 1-10%] CaO has the effect of adjusting the melting point and fluidity of the slag, but if the CaO content in the flux is less than 1%, the bead toe does not conform well and undercuts occur. On the other hand, if it exceeds 10%, the fluidity is poor, the bead height becomes non-uniform, the bead appearance deteriorates, and the slag removability also deteriorates. Therefore, the CaO content in the flux is limited to 1-10%, and preferably 2-8%. [CaF2: 1-10%] CaF2 has the effect of lowering the melting point and viscosity of molten slag, and is an effective component for keeping the bead smooth under welding conditions with large heat input. It also reduces the amount of O (oxygen) in the weld metal and improves toughness. Such effects cannot be obtained if the CaF2 content in the flux is less than 1%. On the other hand, if it exceeds 10%, the viscosity of the molten slag becomes too low, inducing undercut and deteriorating slag removability. Therefore, the CaF2 content in the flux is limited to 1 to 10%. It is preferably 2 to 9%. [Al2O3: 5-20%] Al2O3 is a necessary component for obtaining good slag removability and bead appearance, and also has the effect of improving arc stability. Such effects cannot be obtained if the Al2O3 content in the flux is less than 5%. On the other hand, if it exceeds 20%, the viscosity of the flux increases, resulting in a convex bead and poor slag removability. Therefore, the Al2O3 content in the flux is limited to 5-20%. It is preferably 6-18%. [TiO2: 2-10%] TiO2 is a component that contributes to the removability and low-temperature toughness of the molten slag, and also has the effect of improving the weld bead shape. Such effects cannot be obtained if the TiO2 content in the flux is less than 2%. On the other hand, if it exceeds 10%, the melting point of the molten slag rises too much, and the slag removability deteriorates. Therefore, the TiO2 content in the flux is limited to 2 to 10%. It is preferably 3 to 9%. [Na2O: 1.0-3.0%] Na2O is a component that stabilizes the arc during welding. Such an effect cannot be obtained if the Na2O content in the flux is less than 1.0%. On the other hand, if it exceeds 3.0%, the moisture absorption resistance deteriorates and the amount of diffusible hydrogen in the weld metal increases, inducing low-temperature cracking. Therefore, the Na2O content in the flux is limited to 1.0 to 3.0%, and preferably 1.5 to 3.0%. [B2O3: 0.1-0.5%] B2O3 is a component that contributes to suppressing the formation of grain boundary ferrite, which is a low-toughness structure in the weld metal, and such an effect cannot be obtained if the B2O3 content in the flux is less than 0.1%. On the other hand, if it exceeds 0.5%, a low-melting liquid phase is formed in the weld metal, inducing hot cracking. Therefore, the B2O3 content in the flux is limited to 0.1 to 0.5%, and preferably 0.2 to 0.4%. [Total of CO2 equivalent value of one or more metal carbonates: 2~12%] CO2 generated during welding from metal carbonates such as calcium carbonate (CaCO3) and magnesium carbonate (MgCO3) has the effect of insulating the weld metal from the atmosphere and stabilizing the arc. Such an effect cannot be obtained if the total of the CO2 equivalent values ​​of one or more metal carbonates in the flux ("total" refers only to two or more types; the same applies below) is less than 2%. On the other hand, if it exceeds 12%, the amount of gas becomes excessive, blowing up occurs, and welding workability is deteriorated. Therefore, the total of the CO2 equivalent values ​​of one or more metal carbonates in the flux is limited to 2 to 12%. It is preferably 3 to 10%. In addition to the above, other examples of metal carbonates include potassium carbonate (K2CO3), sodium carbonate (Na2CO3), barium carbonate (BaCO3), and lithium carbonate (Li2CO3).

[0023] [Fe: 15-30%] Fe is effective in improving the welding efficiency and arc concentration. However, if the Fe content in the flux is less than 15%, the welding efficiency decreases and the arc spreads, causing the molten slag to be blown up. On the other hand, if it exceeds 30%, iron grain protrusions are generated on the bead surface, deteriorating the bead appearance. Therefore, the Fe content in the flux is limited to 15-30%, and preferably 17-28%. [Si: 0.1-2.0%] Si is added as metal Si, Fe-Si alloy, etc., and acts as a deoxidizer to reduce the oxygen content in the weld metal. It also has the effect of improving the hardenability of the weld metal. These effects are not realized when the Si content in the flux is less than 0.1%. On the other hand, when it exceeds 2.0%, the strength of the weld metal becomes excessive and the toughness deteriorates. Therefore, the Si content in the flux is limited to 0.1 to 2.0%, and preferably 0.2 to 1.8%. [Mn: 0.1-2.0%] Mn is added as metal Mn or an Fe-Mn alloy, and acts as a deoxidizer to reduce the amount of oxygen in the weld metal. It also has the effect of improving the hardenability of the weld metal. Such an effect is not realized if the Mn content in the flux is less than 0.1%. On the other hand, if it exceeds 2.0%, the strength of the weld metal becomes excessive and the toughness deteriorates. Therefore, the Mn content in the flux is limited to 0.1 to 2.0%, and preferably 0.2 to 1.8%. [Cr: 0.1~4.0%] Cr is added as metallic Cr, Fe-Cr alloy, etc., and is an element that improves the strength of the weld metal. Such an effect cannot be obtained if the Cr content in the flux is less than 0.1%. On the other hand, if it exceeds 4.0%, it leads to coarsening of the structure of the weld metal and reduces toughness. Therefore, the Cr content in the flux is limited to 0.1 to 4.0%, and preferably 0.2 to 3.6%. In the present invention, one or more of Ni, Mo, Al, and Ti may be added to the composition of the flux in the following ranges.

[0024] [Ni:3.0% or less] Ni is added as metallic Ni, Fe-Ni alloy, etc., and is an element that improves the strength and toughness of the weld metal. These effects become prominent when Ni content in the flux is 0.1% or more. On the other hand, if it exceeds 3.0%, it may inhibit the formation of δ-ferrite during solidification of the molten metal and promote segregation, which may induce hot cracking. Therefore, Ni content in the flux is preferably 3.0% or less. More preferably, it is 0.2 to 2.5%. [Mo: 2.0% or less] Mo is added as metal Mo, Fe-Mo alloy, etc., and is an element that suppresses low-toughness grain boundary ferrite in the weld metal. Such an effect is remarkable when Mo in the flux is 0.1% or more. On the other hand, if it exceeds 2.0%, the strength of the weld metal becomes too high, and low-temperature cracking may occur. Therefore, Mo in the flux is preferably 2.0% or less. More preferably, it is 0.2 to 1.6%. [Al: 1.0% or less] Al is added as metallic Al, Fe-Al, etc., and acts as a strong deoxidizer, reducing the amount of oxygen in the weld metal and contributing to improving toughness. This toughness improving effect is remarkable when the Al content in the flux is 0.1% or more. On the other hand, if it exceeds 1.0%, the amount of solid-solubilized Al in the weld metal increases, deteriorating the toughness. Therefore, the Al content in the flux is preferably 1.0% or less. More preferably, it is 0.2 to 0.9%.

[0025] [Ti: 1.0% or less] Ti is added as metallic Ti, Fe-Ti, etc., and acts as a strong deoxidizer, reducing the amount of oxygen in the weld metal and contributing to improving toughness. This toughness improving effect is remarkable when Ti in the flux is 0.1% or more. On the other hand, if it exceeds 1.0%, the amount of solid-solubilized Ti in the weld metal increases, deteriorating toughness. Therefore, Ti in the flux is preferably 1.0% or less, and more preferably 0.2 to 0.9%. The remaining components in the flux composition other than those mentioned above are unavoidable impurities such as Ba, Li, P, and S. Of these unavoidable impurities, Ba and Li are each preferably limited to 3.0% or less, and in particular, P and S, which affect the welding quality, are each preferably limited to 0.1% or less. [Flux manufacturing method] The flux used in the present invention is preferably a sintered flux with a relatively high basicity in order to obtain a weld metal with high strength and toughness. The manufacturing method thereof includes a method in which raw material powder is blended so as to obtain a flux composition suitable for the present invention, kneaded with a binder (water glass), granulated, sintered, and subjected to a sizing treatment. Although not particularly limited, the sintering temperature is, for example, 400 to 800°C, and the particle size after sizing treatment is, for example, 2.5 mm or less. EXAMPLES

[0026] Hereinafter, the present invention will be described in more detail with reference to examples. However, the following examples are merely intended to illustrate and explain the present invention in more detail, and are not intended to limit the scope of the present invention.

[0027] The base material was a 590 MPa-class steel plate with the plate thickness, composition (the balance being Fe and unavoidable impurities) and tensile properties shown in Table 1. The groove shape was a two-stage V groove shape with a root face of 2 mm and groove angles of 35° in the first stage and 60° in the second stage, as shown in Figure 1.

[0028] The welding wire used was a 6.4 mmφ welding wire produced by melting molten steel having the composition shown in Table 2 (the balance being Fe and unavoidable impurities) in a vacuum melting furnace, casting it into a 300 kg steel ingot, heating it to 1000°C, hot rolling it, and then cold rolling it.

[0029] The flux was prepared by compounding the raw material powders to obtain the composition shown in Table 3, kneading them with a binder (water glass), granulating them, and firing them at 500°C. The particles were then subjected to a granulation process, including removing dust and crushing large particles, to adjust the particle size to 2.5 mm or less.

[0030] Submerged arc welding shall be performed using welding conditions I shown in Table 4 or welding conditions II shown in Table 5. As shown in Fig. 2, a total of four passes were performed: a first pass P1, a second pass P2, a third pass P3, and a fourth pass P4. Note that there was no preheating and the interpass temperature was 150±10°C. Submerged arc welding was performed using the steel plates, welding wire, flux, and welding conditions shown in Table 6, and submerged arc welded joints were produced.

[0031] After welding, a test piece was taken from the center of the groove width of the weld metal, 10 mm below the surface of the steel plate, and an elemental analysis was performed using wet analysis. The cross-sectional macro of the welded joint was also observed with an optical microscope to determine the presence or absence of cracks. If cracks were found in the weld metal, it was rated as "cracks present," and if no weld defects were found, it was rated as "cracks absent." The width of the heat-affected zone formed by the final pass, 10 mm below the surface of the steel plate, was also measured.

[0032] Also, as shown in Figure 3, a tensile test piece 10 (parallel part diameter 12.5 mmφ) was taken from a position 10 mm below the surface of the steel plate 1 at the center of the groove width of the weld metal, and a tensile test was performed in accordance with JIS Z2241. Also, as shown in Figure 4, a Charpy impact test piece 11 (cross section 10 mm square, 2 mm V notch) was taken from a position 7 mm below the surface of the steel plate 1 at the center of the groove width of the weld metal, and an impact test was performed at a test temperature of 0°C in accordance with JIS Z2242.

[0033] The results are summarized in Table 7 (the balance of the weld metal composition is Fe and unavoidable impurities).

[0034] As shown in Table 7, in the examples of the present invention, no cracks were observed, and the yield strength (0.2% proof stress) at room temperature was 500 MPa or more, the tensile strength was 590 MPa or more, and the strength was high. V E0℃ is 47J or more. In addition, the heat input of each pass is 100kJ / cm or more (Table 4, Table 5), the interpass temperature is 150±10℃, and the holding time between passes is 1 hour or less, which is a highly efficient welding. In other words, in the present invention, the strength and toughness of the weld metal required for high efficiency are ensured.

[0035] On the other hand, in the comparative examples outside the scope of the present invention, the required strength and toughness of the weld metal were not obtained due to at least one of the occurrence of cracks, insufficient strength and insufficient toughness.

[0036] [Table 1]

[0037] [Table 2]

[0038] [Table 3]

[0039] [Table 4]

[0040] [Table 5]

[0041] [Table 6]

[0042] [Table 7]

[0043] In Table 7, in Example 3 (Comparative Example), the wire C and flux c used were within the preferred composition ranges, but the Si and Cr contents of both the wire and flux were low (Tables 2, 3, and 6). Therefore, the Cr content of the weld metal was below the lower limit, and the SRI was also below the lower limit.

[0044] In Example 9 (Comparative Example), the flux i used exceeded the upper limit of the suitable composition range for B2O3 (Tables 3 and 6), and therefore the B content of the weld metal exceeded the upper limit.

[0045] In Example 10 (Comparative Example), the wire B and flux c used were within the preferred composition ranges, but the Si and Cr contents of both the wire and flux were low (Tables 2, 3, and 6). Therefore, although the composition of the weld metal satisfied the range of the present invention, the SRI of the weld metal was below the lower limit.

[0046] In Example 12 (Comparative Example), the flux i used exceeded the upper limit of the suitable Cr composition range (Tables 3 and 6), and therefore the Cr content of the weld metal exceeded the upper limit.

[0047] In Example 13 (Comparative Example), the flux k used was above the upper limit of the suitable composition range for Mo (Tables 3 and 6), and therefore the Ceq of the weld metal exceeded the upper limit. [Explanation of symbols]

[0048] 1 steel plate 2 Backing material 10 Tensile test specimen 11 Charpy impact test piece

Claims

1. In multi-layer submerged arc welded joints, The composition of the weld metal is expressed as mass percent. C: 0.04-0.12%, Si:0.10~0.50%, Mn: 1.0 to 1.8%, P: 0.025% or less, S: 0.015% or less, Cr:0.2~1.0%, Mo: 0.2-1.0%, Ti:0.002~0.070%, B:0.0004-0.0025%, O: 0.050% or less, A submerged arc welded joint comprising: N: 0.008% or less, the balance being Fe and unavoidable impurities; Ceq represented by the following formula (1) being 0.44 to 0.56; and SRI represented by the following formula (2) being 30 or more. Ceq=C+Si / 24+Mn / 6+Ni / 40+Cr / 5+Mo / 4+V / 14 (1) SRI=[Si]×[Cr]×[Mo]×1000 (2) In formula (1), C, Si, Mn, Ni, Cr, Mo, and V represent the content (mass%) of each element in the composition of the weld metal, and the content of elements that are not contained is 0. In formula (2), [Si], [Cr], and [Mo] represent the numerical values ​​(dimensionless) of mass% of each element.

2. The composition of the weld metal is further comprised in mass percent:

2. The submerged arc welded joint according to claim 1, characterized in that it contains one or more of the following: Cu: 0.60% or less, Ni: 1.8% or less, V: 0.05% or less, Nb: 0.05% or less, and Al: 0.05% or less.

3. 3. A submerged arc welded joint according to claim 1, characterized in that the width of the heat affected zone within 10 mm of the surface formed by the final welding pass is 5 mm or more.

4. 2. The method for producing a submerged arc welded joint according to claim 1, The composition of the welding wire is expressed as mass percent: C: 0.02-0.14%, Si:0.02~0.80%, Mn: 1.0 to 2.3%, P: 0.025% or less, S: 0.015% or less, Mo: 0.2-1.0%, O: 0.020% or less, N: 0.010% or less, the balance being Fe and unavoidable impurities; And the composition of the welding flux is, in mass%, Yes 2 :8~30%, MgO: 10-30%, CaO: 1 to 10%, CaF 2 :1~10%、 <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :5~220%、 TO 2 :2~10%, Na 2 O:1.0~3.0%、 B 2 O 3 :0.1~0.5%、 One or more metal carbonates 2 Total conversion value: 2-12%, Fe: 15-30%, Si: 0.1-2.0%, Mn: 0.1-2.0%, A method for producing a submerged arc welded joint, comprising the steps of: Cr: 0.1 to 4.0%; and the balance consisting of unavoidable impurities.

5. 3. The method for producing a submerged arc welded joint according to claim 2, The composition of the welding wire is expressed as mass percent: C: 0.02-0.14%, Si:0.02~0.80%, Mn: 1.0 to 2.3%, P: 0.025% or less, S: 0.015% or less, Mo: 0.2-1.0%, Contains O: 0.020% or less, N: 0.010% or less, Further, it contains one or more of Cu: 1.00% or less, Ni: 2.5% or less, Cr: 1.0% or less, V: 0.10% or less, Nb: 0.10% or less, Al: 0.05% or less, Ti: 0.060% or less, and B: 0.0050% or less, with the balance being Fe and unavoidable impurities; The composition of the welding flux is in mass percent, Yes 2 :8~30%, MgO: 10-30%, CaO: 1 to 10%, CaF 2 :1~10%、 <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :5~220%、 TO 2 :2~10%, Na 2 O:1.0~3.0%、 B 2 O 3 :0.1~0.5%、 One or more metal carbonates 2 Total conversion value: 2-12%, Fe: 15-30%, Si: 0.1-2.0%, Mn: 0.1-2.0%, Cr: 0.1 to 4.0%; The method for producing a submerged arc welded joint further comprises one or more of the following: Ni: 3.0% or less; Mo: 2.0% or less; Al: 1.0% or less; and Ti: 1.0% or less, with the balance being unavoidable impurities.

Citation Information

Patent Citations

  • Bond flux for submerged arc welding

    JP2000107885A

  • Large heat input butt welded joint superior in brittle fracture characteristic resistance

    JP2005125348A

  • Method for producing spiral steel tube, and spiral steel tube

    JP2011161500A

  • Welded metal superior in hydrogen embrittlement resistance sensitivity

    JP2014133258A

  • Bent steel tube

    JP2021130830A